A new method for determining the magnetic properties of solid materials employed in unconventional magnetic circuits - Mohammed, A.; Cox, Tom; Galea, Michael; Gerada, C. (Institute of Electrical and Electronics Engineers, 2017)
The mechanical and thermal properties of common, solid (non-laminated) ferromagnetic materials are widely available, but the electro-magnetic characteristics of such solid materials are often undefined. Existing characterization procedures such as the toroidal ring sample test method are capable of mapping the electro-magnetic properties of solid materials quite accurately when investigating materials to be used in conventional magnetic circuits, i.e. where the flux paths and induced eddy currents follow the more common ‘radial’ characteristics as in a standard rotating machine. When solid ferromagnetic material is employed in unconventional machine structures, such as for transverse flux machines or tubular linear machines, simple toroidal test methods do not accurately represent the flux conditions in the stator material. In this paper a new testing method is proposed to accurately impose the correct flux conditions for tubular linear machines. The proposed method uses a simple experimental test setup to characterize the magnetic properties of solid, ferro-magnetic material. The basic experimental results from the new setup are compared to results from 3D finite element analysis.